English Education Students’ Challenges Integrating Literature in Theses - Nisa Arrizki; Hidayat, Aang Fitro; Nurbani, Armelia Nungki (Universitas Nusantara PGRI Kediri, 2025)
The study addresses the pervasive difficulties students encounter in locating appropriate, current, and topic-specific literature, synthesizing existing research with their own arguments, maintaining narrative cohesion, and navigating the complexities of the literature review chapter. A significant concern is the increasing reliance on AI tools and the associated ethical considerations. This research aims to identify and examine the specific challenges of English language Education students face in integrating literature sources, such as improper paraphrasing, overreliance on direct quotations, ineffective synthesis, and limited understanding of citation conventions. It also seeks to explore underlying causes like insufficient academic writing training, low language proficiency confidence, and lack of familiarity with scholarly literature. A qualitative narrative inquiry approach was employed, involving semi-structured interviews with four eighth-semester undergraduate students from the English Language Education Department. Data were analyzed using narrative analysis to understand participants' experiences, perceptions, and strategies in navigating literature integration challenges. Trustworthiness was the validation variable used in this investigation. Findings reveal that students struggle with finding relevant sources, adjusting quotes to fit personal arguments, and maintaining narrative cohesion, with the literature review consistently identified as the most challenging section. While AI tools like ChatGPT are perceived as effective for efficiency and ideal generation, ethical considerations regarding plagiarism are crucial. Students effectively use conceptual maps and matrices for organization. The study concludes with a strong demand for practical support, including workshops and resources, to enhance literature integration skills, emphasizing the urgent need for targeted pedagogical interventions to improve thesis quality.